1995
DOI: 10.1210/en.136.4.1495
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotestosterone is the active androgen in the maintenance of nitric oxide-mediated penile erection in the rat

Abstract: Androgens are essential for the expression of normal libido in the male, but their role in the maintenance of the erectile response in humans is controversial. It has been shown previously in the rat that castration induces 1) loss of penile reflexes; and 2) considerable reduction in the erectile response to electric field stimulation (EFS) of the cavernosal nerve. Both of these effects can be reversed by testosterone replacement. The current study was performed to determine whether these testosterone effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
1
6

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 0 publications
4
113
1
6
Order By: Relevance
“…DHT capsules of this size have been reported to produce circulating DHT levels in the physiological range [41,42,43] and were behaviorally effective in another study in which we used identical DHT capsules s.c. and found that mating occurred if male rats were given either E 2 or BSA-E 2 implants to the MPO, whereas DHT-treated males with vehicle MPO implants did not mate [44]. Thereafter, they were stereotaxically implanted bilaterally with 22-gauge stainless steel, ethylene oxide sterilized guide cannulae (Plastics One) aimed at the MEA (level skull coordinates: AP = –3.2 mm, ML = ± 3.5 mm, DV = –8.2 mm [39]).…”
Section: Methodsmentioning
confidence: 99%
“…DHT capsules of this size have been reported to produce circulating DHT levels in the physiological range [41,42,43] and were behaviorally effective in another study in which we used identical DHT capsules s.c. and found that mating occurred if male rats were given either E 2 or BSA-E 2 implants to the MPO, whereas DHT-treated males with vehicle MPO implants did not mate [44]. Thereafter, they were stereotaxically implanted bilaterally with 22-gauge stainless steel, ethylene oxide sterilized guide cannulae (Plastics One) aimed at the MEA (level skull coordinates: AP = –3.2 mm, ML = ± 3.5 mm, DV = –8.2 mm [39]).…”
Section: Methodsmentioning
confidence: 99%
“…Administration of 5α-DHT with or without the 5α-RIs, 17βTC, restored sexual behavior in long-term castrated male rats and mice suggesting a critical role for 5α-DHT in erectile physiology [29]. Further animal studies showed castration resulted in 50% reduction in erectile response, which was reversed by T treatment [30]. However, treatment with T together with finasteride did not restore the erectile response in castrated animals, suggesting that 5α-DHT is an important hormone in erectile physiology.…”
Section: Introductionmentioning
confidence: 99%
“…DHT capsules of this size have been reported to produce circulating DHT levels in the physiological range [41,42,43]. Thereafter, they were stereotaxically implanted bilaterally with 22-gauge stainless-steel, ethylene oxide-sterilized, guide cannulae (Plastics One, Roanoke, Va., USA) aimed at the MPO (level skull coordinates: anterior-posterior = –0.5 mm, medial lateral = ± 0.75 mm, dorsal-ventral = –8.0 mm [44]).…”
Section: Methodsmentioning
confidence: 99%